PENGEMBANGAN BAHAN AJAR BERBASIS SAINTIFIK UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA DI SEKOLAH DASAR - Zifanna Ardina; Sukmawarti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to develop scientific-based teaching materials to improve elementary school students' mathematics learning outcomes, especially in flat geometry material in grade IV. The background of this study is based on the low mathematics learning outcomes of students caused by the assumption that mathematics is a difficult subject, the lack of interesting teaching materials, and the lack of a scientific approach in the learning process. The type of research used is research and development (Research and Development) with a 4D model consisting of the Define, Design, Development, and Dissemination stages. The subjects of this study were 20 fourth-grade students of Kasih Ibu Private Elementary School, Medan. Data collection instruments consisted of observation, interviews, expert validation questionnaires, and learning outcome tests. The validation results showed that the developed teaching materials were included in the categories of